A radiological description of bone tissue regeneration in intraosseal distraction osteosynthesis with driving devices. Recommended modes of distraction - Dragan, Volodymyr; Andrianov, Mykhaylo; Goncharova, Larisa; Tkach, Andrey; Plotkin, Andrey; Shpuntov, Olexey; Fedulichev, Pavlo; Herman, Olexiy; Daniluk, Andrey; Kuznetsov, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Radiological development in the formation of distraction regenerate in the process of intraosseal distraction osteosynthesis was analysed and optimum distraction modes with driving devices were recommended.